2017
DOI: 10.1080/02640414.2017.1361894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inter-limb asymmetries on physical and sports performance: a systematic review

Abstract: The prevalence of inter-limb asymmetries has been reported in numerous studies across a wide range of sports and physical qualities; however, few have analysed their effects on physical and sports performance. A systematic review of the literature was undertaken using the Medline and SPORT Discus databases, with all articles required to meet a specified criteria based on a quality review. Eighteen articles met the inclusion criteria, relating participant asymmetry scores to physical and sports performance meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
367
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 309 publications
(400 citation statements)
references
References 63 publications
24
367
1
8
Order By: Relevance
“…Consequently, practitioners who measure between-limb asymmetries from jump tests should be mindful of differences ~12% and aim to quantify whether they are associated with any decrements in performance. This seems prudent advice given the notion that asymmetries > 10% have been suggested to potentially impact physical and sports performance (7,9) and the results of the present study are in agreement with this consensus. Cumulatively, given that the SLCMJ appears more sensitive at identifying inter-limb differences and shows stronger relationships to decrements in sprint speed compared to horizontal hops, these results indicate that the SLCMJ may be the most appropriate jump test to identify the prevalence of interlimb asymmetries in athletes.…”
Section: Statistical Analysessupporting
confidence: 89%
“…Consequently, practitioners who measure between-limb asymmetries from jump tests should be mindful of differences ~12% and aim to quantify whether they are associated with any decrements in performance. This seems prudent advice given the notion that asymmetries > 10% have been suggested to potentially impact physical and sports performance (7,9) and the results of the present study are in agreement with this consensus. Cumulatively, given that the SLCMJ appears more sensitive at identifying inter-limb differences and shows stronger relationships to decrements in sprint speed compared to horizontal hops, these results indicate that the SLCMJ may be the most appropriate jump test to identify the prevalence of interlimb asymmetries in athletes.…”
Section: Statistical Analysessupporting
confidence: 89%
“…Additionally, no studies to date have reported inter-positional throwing and non-throwing arm compositional comparisons (i. e., fat, lean soft tissue, and bone masses). These compositional comparisons are important given that contralateral asymmetries may increase injury risk [7,8]. In addition, no studies to date have reported visceral adipose tissue (VAT) mass measurements in a collegiate softball athlete population.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous literature investigating the differences between the ISQ and IMTP have only used a bilateral stance. 4,21 Given the increased frequency of research pertaining to measurement of unilateral tasks, 2,3 and their associations with reductions in performance, 3 a more comprehensive understanding of these assessment modes is warranted.…”
Section: Introductionmentioning
confidence: 99%